Advantageous comparison: using Twitter responses to understand similarities between cybercriminals ("Yahoo Boys") and politicians ("Yahoo men"). Issue 11 (November 2022) - Lazarus, Suleman; Button, Mark; Adogame, Afe
Abstract: This article is about the manifestations of similarities between two seemingly distinct groups of Nigerians: cybercriminals and politicians. Which linguistic strategies do Twitter users use to express their opinions on cybercriminals and politicians? The study undertakes a qualitative analysis of 'engaged' tweets of an elite law enforcement agency in West Africa. We analyzed and coded over 100, 000 'engaged' tweets based on a component of mechanisms of moral disengagement (i.e., advantageous comparison), a linguistic device. The results reveal how respondents defend the actions of online fraudsters ("the deviant group") by strategically comparing them to the wrongful acts of corrupt politicians ("the respectable group"). Similarly, the results show how respondents positioned this linguistic strategy to compare "the powerless group" (online fraudsters) and "the powerful group" (politicians) in society. Indeed, tweet responses suggest that the Economic and Financial Crimes Commission (EFCC) generally looks downwards for culprits (i.e., online fraudsters) while ignoring fraudulent politicians. We conclude that the process by which some actions are interpreted as a crime compared to others is a moral enterprise. Abstract : Twitter; Online fraud; Tweets; Yahoo Boys; Corruption; Cybercrime; Nigeria; Moral disengagement mechanism; Rationalization; 419 and scams.